A homologue of yeast acyl-CoA synthetase Faa1 contributes to cytomembrane functionality involved in development and virulence in the insect pathogenic fungus Beauveria bassiana. (March 2022) - Li, Xiu-Hui; Peng, Yue-Jin; Ding, Jin-Li; Feng, Ming-Guang; Ying, Sheng-Hua
Abstract: Acyl-CoA synthetase (ACS) functions as a hub linking lipid metabolism with in cellular physiologies by producing active intermediate of catalyzes acyl-CoA. However, the biological roles of ACS are largely unknown in filamentous fungi. In this study, an ortholog of yeast Faa1, named BbFaa1, was functionally characterized in the filamentous entomopathogenic fungus Beauveria bassiana . BbFaa1 was associated with vesicular membrane, and its loss resulted in the impaired cytomembrane integrity. Notably, in Δ Bbfaa1 mutant strain, the translocation of hydrophobins across cell membrane was significantly hampered, which resulted in the reduced hydrophobicity of aerial mycelia and conidia. In addition, loss of BbFaa1 significantly weakened fungal virulence. Our findings indicate that the metabolism of acyl-CoA synthetase Faa1 contributes to the cytomembrane functionality which cascades hydrophobin translocation and differentiation, thus affecting virulence of B. bassiana . Graphical abstract: Image 1 Highlights: Beauveria bassiana Faa1 (BbFaa1) localizes on the plasma and vacuolar membranes. BbFaa1 contributes to the cytomembrane functionality. BbFaa1 is involved in the hydrophobin translocation across cytomembrane. BbFaa1 links lipid metabolism to fungal hydrophobicity and virulence.